2012
DOI: 10.1111/j.1471-6712.2012.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ lived experiences of a reduced intake of food and drinks during illness: a literature review

Abstract: Patients expect committed nursing care in regard to nutritional advice during illness and assistance in meal-related situations. Nurses need to refocus on fundamental caring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…The number of reviews with low/moderate and high risk of bias according to the 12 domains is presented in Table . The main characteristics of reviews with low/moderate risk of bias are described in Table and the 18 reviews with high risk of bias are reported in Table . Table presents the 163 excluded reviews and the main reason for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of reviews with low/moderate and high risk of bias according to the 12 domains is presented in Table . The main characteristics of reviews with low/moderate risk of bias are described in Table and the 18 reviews with high risk of bias are reported in Table . Table presents the 163 excluded reviews and the main reason for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, one systematic review was identified describing the opinions of older persons regarding eating conditions, but was excluded due to high risk of bias. The older persons requested tailored advice about nutrition and support from their caregivers to avoid negative experiences and embarrassment at mealtimes . Dry mouth, which is a common condition among older persons as a side effect of medications and oral motor function, affects speech, chewing and swallowing, which can in turn influence their nutritional status .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This involves early oral feeding, plenty of oral supplements, nutritional counselling and nutritional therapy when nutritional risk is established (Weimann et al, ). In a literature review by Larsen and Uhrenfeldt (), it is described how patients in four out of 13 articles did not have an experience of receiving the expected advice and nutritional counselling when having eating difficulties during hospitalisation (Larsen & Uhrenfeldt, ). Furthermore, this is in line with a study by Boaz et al (), which examined nurses’ knowledge and attitudes regarding nutrition care (Boaz et al, ).…”
Section: Critical Interpretation and Discussionmentioning
confidence: 99%
“…For instance, the sudden dance event, the change of soundscape at the wards, and the introduction of home-made meatballs created possibilities for shifting host-guest roles and sociability between patients. Sociability as a means of increasing hospital meal experiences and food intake among undernourished patients has been emphasized in several hospital studies (Hartwell, Shepherd and Edwards 2013, Holm, Smidt 2000, Edwards, Hartwell 2004, Larsen, Uhrenfeldt 2012, Johns, Hartwell and Morgan 2010.…”
Section: Discussion -Possibilities For Hospitalityscapes Within Hospimentioning
confidence: 99%